Brunei Darussalam : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
In this study, the following are discussed: nominal GDP by economic activity and expenditure, quarterly nominal GDP by economic activity and expenditure, composition of nominal GDP by economic activity and expenditure, quarterly composition of nominal GDP by economic activity and expenditure, real GDP by economic activity and expenditure, quarterly real GDP by economic activity and expenditure, growth in real GDP by economic activity and expenditure, growth in quarterly real GDP by economic activity and expenditure, oil and gas production and sales, and government and private sector employment.